Noise Level Analysis of KM. Sabuk Nusantara 71 to Increase Ship Passengers Comfort Based on BKI Rules - Sunarso Sugeng; Mohammad Ridwan; Sulaiman Sulaiman; Samuel Febriary Khristyson (TEKNIK, 2021)
Noise is an unwanted sound or sound source which can distract or harm human health and comfort. According to experts, a sound that exceeds the level of human listening senses can cause deafness. Such danger can also be found in ships. An alternative to reduce noise in ships is by modifying the construction.  This research aims to compare noising before and after adding a side deck girder in the engine room of a 2000 DWT ship. The result showed that in the engine room, after adding a FB 180 x 8 mm FP 75 x 10 mm sized T profile, for 0-30 seconds intervals, the maximum noise was down from 127 dB to 62 dB or a 0.47% decrease. Meanwhile, the maximum noise was down from 98.6 dB to 57 dB in the accommodation room or decreased by 0.41%. The maximum noise was down from 83 dB to 37 dB or a 0.56% decrease in the navigation room. Such modification had reduced the average noise range from 80-40 dB to 55-20 dB.